EVENT MANAGEMENT ONLINE: A PROMISING MARKETING TECHNOLOGY TO PROMOTE A UNIVERSITY ON THE MARKET OF EDUCATIONAL SERVICES - Kuzmenko, (Revista Inclusiones, 2020)
Changing the consumer model under the influence of new information technologies requires an adequate marketing response of educational institutions. When promoting educational services, innovations in the field of event management are relevant. This opens up prospects for a special event method in virtual space. The material for studying the effectiveness of event management in the virtual space was special research works, as well as the websites of event companies in Moscow. The research methodology is based on market marketing methods. The perspective of organizing online events for the University's marketing policy is shown. The organization of management of University events in online mode is considered. The effectiveness of intellectual team building during such events is shown. Event management online has a technological advantage over traditional methods of promoting educational services. Thanks to new information technologies, this increases the effectiveness of advertising and positively affects the formation of a loyal audience. In the conditions of high competition between universities in the world market of educational services the organization of events in online mode will allow the University to significantly increase its share in it.